Correlation of serum albumin levels with the grading of esophageal varices - Avinash H Rajanna; Ijantkar, Sandeep; Vaibhav S Bellary (Asian Journal of Medical Sciences, 2023)
Background: Variceal bleed is one of the major complications seen in patients with cirrhosis of liver of various etiologies and endoscopy is a gold standard for its diagnosis which is an invasive procedure. There are other modalities of non-invasive methods to determine the degree of varices and estimation of serum albumin levels in one among them. Aims and Objectives: The aims of this study were as follows: (1) To measure serum albumin levels in patients with cirrhosis of liver and (2) to correlate serum albumin levels with grading of esophageal varices. Materials and Methods: A cross-sectional study was conducted on a total of 100 patients in Bangalore during the study period from October 2016 to September 2017. Case record form with follow-up chart was used to record the duration of disease, history of treatment and complications. Patients underwent biochemical investigations and endoscopy. The presence of varices and their size was obtained from endoscopy reports. Results: Study includes 100 patients that majority belonged to the age group 40–49 years (46%). Serum albumin levels of <2.8 mg/dL was seen in high number of study subjects (76%). Forty patients had albumin levels of <2.8 mg/dL with grade 3 OGD scopy, followed by 23 patients with Grade 1 esophagogastroduodenoscopy (OGD scopy). The association between albumin and OGD scopy grades was found to be significant (P=0.027). Conclusion: We conclude that low albumin levels predict higher grades of esophageal varices. It can identify the subset of patients who require prophylactic endoscopic management. Estimating serum albumin levels are non-invasive that can screen the patient for esophageal varices. Thus, this reduces the economic burden on the patients and the cost of management of esophageal varices.